Collapse of the Opposition Inter-Party Coalition in Uganda - Catherine Promise Biira (Graduate Institute Publications, 2013)
"It's not so much what you agree upon, what you write on paper, but something intangible that in the end determines the success of political cooperation," stated the leader of the Uganda People's Congress Dr. Olara Otunnu. Hoping to put an end to the dominant-party system of Uganda - where President Yoweri Museveni and his National Resistance Movement had ruled since 1986 - in 2008, four parties of the opposition gathered under the banner of the Inter-Party Cooperation (IPC). Their intention ...